2008
DOI: 10.2137/145960609790059578
|View full text |Cite
|
Sign up to set email alerts
|

Legumes in Finnish agriculture: history, present status and future prospects

Abstract: Legumes are important in world agriculture, providing biologically fixed nitrogen, breaking cereal disease cycles and contributing locally grown food and feed, including forage. Pea and faba bean were grown by early farmers in Finland, with remains dated to 500 BC. Landraces of pea and faba bean were gradually replaced by better adapted, higher quality materials for food use. While grain legumes have been restricted by their long growing seasons to the south of the country, red, white and alsike clovers are na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…In many countries, legume plants have recently been receiving increasing attention from researchers and growers (Hauggaard-Nielsen et al 2009, Mariotti et al 2009, Stoddard et al 2009, Mikić et al 2010. Pea (Pisum sativum L.) is the most common legume in crop rotations and quite productive in temperate conditions, as well as in Lithuania (Auskalnis 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, legume plants have recently been receiving increasing attention from researchers and growers (Hauggaard-Nielsen et al 2009, Mariotti et al 2009, Stoddard et al 2009, Mikić et al 2010. Pea (Pisum sativum L.) is the most common legume in crop rotations and quite productive in temperate conditions, as well as in Lithuania (Auskalnis 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the average faba bean cultivation area is close to 2.5 million hectares annually, which ranks fourth among cool-season crops [2]. It has been demonstrated that growing faba bean is the most effective strategy for managing soil fertility through crop rotation, which contributes to sustainable agriculture [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peas and other domestic legumes offer the possibility to improve self-sufficiency in protein-rich feedstuffs (Gatel 1994). They have an important role in the crop rotation particularly in organic farming due to their ability to fix nitrogen (Stoddard et al 2009). …”
Section: Introductionmentioning
confidence: 99%